129k views
2 votes
How do I use the Pythagorean Theorem with square roots??

plz help i don't even have a grade in math ._.

User Stael
by
4.9k points

1 Answer

3 votes

Pythagorean theorem is


{a}^(2) + {b}^(2) = {c}^(2)

Say a triangle looked like the attached picture.

To solve for x, plug the values into the pythagorean theorem.


{x}^(2) + { √(2) }^(2) = {3}^(2)


{x}^(2) + 2 = 9


{x}^(2) = 7


x = √(7)

If you need any more help then reply to this with a comment!

How do I use the Pythagorean Theorem with square roots?? plz help i don't even have-example-1
User Vanni Totaro
by
6.0k points